Sustaining Employee Owned Companies: Seven Recommendations - Sauser, William I. (Journal of business ethics, 2009)
The employee owned company (EOC) might be the ideal blend of capitalism and communitarianism that vitalizes the global economy. EOCs – based on the concepts of employee participation and control – have sprung up in the United Kingdom, some parts of the European Union, the United States, Japan, and the former Eastern Bloc countries. Research has shown that they are able to compete effectively with more traditional companies. However, in addition to the pressures of business competition, EOCs face two other key problems as they strive to survive: (1) degeneration and (2) human nature and the abuse of power. After introducing the idea of the EOC and describing briefly these two key problems, this article presents seven recommendations for sustaining employee owned companies. These recommendations – grounded in sound organizational theory and the writings of experts in the field of employee ownership – are offered as hypotheses to be examined empirically by future researchers.